Clinical Efficacy and Safety of Combination Drug Therapy in Patients with Multimorbidity - Shoymardonovich, Namozov Begali (American Journal of Biomedicine and Pharmacy, 2026)
Multimorbidity, defined as the coexistence of two or more chronic diseases in a single patient, presents a major challenge to modern healthcare systems. Combination drug therapy is frequently required to control multiple pathological processes simultaneously; however, it increases the risk of adverse drug reactions, drug–drug interactions, and reduced treatment adherence. This study evaluates the clinical efficacy and safety of combination pharmacotherapy in patients with multimorbidity, focusing on therapeutic outcomes, incidence of adverse events, and overall patient stability. A prospective observational study was conducted involving patients with cardiovascular, metabolic, and inflammatory comorbidities receiving standardized combination drug regimens. Clinical parameters, laboratory indicators, and patient-reported outcomes were monitored over a 24-month period. Results demonstrated that rationally selected combination therapy significantly improved disease control and functional status while maintaining an acceptable safety profile. Careful medication selection, dose adjustment, and continuous monitoring were critical in minimizing adverse effects. The findings support the use of individualized, evidence-based combination drug therapy as an effective and safe approach for managing patients with multimorbidity.